Gerald McBoing Boing - Seuss, Dr.; Crawford, Mel (New York : Random House, 2000)
Much to the distress of his parents and classmates, the only way Gerald communicates is through boings, toots, and whistles.
"Based on the Academy Award-winning motion picture.".
Kirkus Review.
Publisher's Weekly.
4.0.
4.0
K-3
Keywords: Communication -- Fiction; Individuality -- Fiction; Sounds -- Fiction; Stories in rhyme; Communication -- Fiction; Individuality -- Fiction; Sounds -- Fiction; Stories in rhyme